Hubungan Pengetahuan dengan Pemilihan KB Suntik Di Wilayah Kerja UPTD Puskesmas Bumi Agung Kota Pagar Alam: Hubungan Pengetahuan dengan Pemilihan KB Suntik Di Wilayah Kerja UPTD Puskesmas Bumi Agung Kota Pagar Alam - Mika Oktarina; Yuni Ramadhaniati; Puteri Andika; Melati Melati (Yayasan Ahmad Mansyur Nasirah, 2022)
Introduction: Injectable hormonal contraception is one of the contraceptives that are widely used because of it is effectiveness, practical use, relatively cheap and safe; this study aims to determine the relationship between knowledge and the selection of injectable family planning in the working are of UPTD Bumi Agung Health Center, Pagar Alam City. This study used an analytical survey with a cross sectional method. The population is all acceptors who actively use the same contraseption for one year who visited the working area of UPTD Bumi Agung Health Center Pagar Alam City. As many as 363 people, sample of 78 people using purposive sampling technique. Data collection is primary and secondary data. The analysis technique used univariate and bivariate (Chi square). The results of this study were obtained: (1) From 78 respondents, who chose to use injectable contraception 35 respondents; (2) From 78 respondents, 40 respondents have good knowledge; (3) There is a significant relationship between mother's knowledge and the selection of injectable family planning in the working area of UPTD Bumi Agung Health Center, Pagar Alam City, with a strong relationship category. It is expected that the Health Center will maximize the family planning services, especially injectable family planning and explain the advantages of injectable family planning, so that mothers who do not use family planning program and still have the potential of experiencing the fertility can use injectable famili planning program. Pendahuluan: Kontrasepsi hormonal KB suntik merupakan salah satu kontrasepsi yang banyak dipakai, karena kerjanya yang efektif, pemakaiannya yang praktis, harganya relatif murah dan aman;Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dengan pemilihan KB suntik di wilayah kerja UPTD Puskesmas Bumi Agung Kota Pagar Alam. Penelitian ini menggunakan survey analitik dengan metode cross sectional. Populasi adalah seluruh akseptor KB yang aktif menggunakan KB yang sama selama satu tahun yang berkunjung ke Wilayah Kerja UPTD Puskesmas Bumi Agung Kota Pagar Alam sebanyak 363, sampelsebanyak 78 orang, dengan tehnik purposive sampling. Pengumpulan data yaitu data primer dan sekunder. Teknik analisis menggunakan Univariat dan bivariat (Chi square). Hasil penelitian ini didapatkan: (1) Dari 78 responden yang memilih menggunakan KB suntik sebanyak 35 responden memilih menggunakan KB suntik; (2) Dari 78 respondensebanyak 40 responden memiliki pengetahuan baik.; (3) Ada hubungan yang signifikan antara pengetahuan ibu dengan Pemilihan KB Suntik di Wilayah Kerja UPTD Puskesmas Bumi Agung Kota Pagar Alam, dengan kategori hubungan kuat. Diharapkan pihak puskesmas lebih memaksimalkan pelayanan KB, khususunya KB suntik dan menjelaskan kelebihan KB suntik, sehingga ibu-ibu yang tidak menggunakan KB dan masih berpoptensi mengalami fertilitas dapat menggunakan KB suntik.